Improving The Knowledge and Skills of Posyandu Cadres Regarding Diabetes Mellitus: An Efforts to Strengthen Primary Service Integration at the Tahtul Yaman Community Health Centre, Jambi City - Shafira, Nyimas Natasha Ayu; Enis, Rina Nofri; Maharani, Citra; Fitri, Amelia Dwi; Perkasa, Tengku Arief Buana; Amatullah, Afifah; Hasmita, Debby (Universitas Jambi, 2025)
ABSTRACT Diabetes mellitus (DM) is a significant public health challenge, with a rapidly increasing burden in Indonesia. Community health cadres (kader) are crucial for community-level prevention, yet many possess limited knowledge regarding DM management and prevention. This community engagement program aimed to enhance the knowledge, attitudes, and practices (KAP) of health cadres within the Tahtul Yaman Primary Health Center area in Jambi City, focusing on diabetes prevention and control. This program utilized a participatory action research approach involving 15 active community health cadres. The intervention, conducted between August and September 2025, consisted of structured training modules, interactive lectures, Focus Group Discussions (FGDs), skill-based simulations (including glucometer use), and the distribution of educational toolkits. A pre-test/post-test design was used to evaluate changes in knowledge, with data analyzed using the Wilcoxon signed-rank test. Qualitative data were gathered through reflection sessions and one-month post-training field observations. Participants showed a statistically significant improvement in knowledge regarding diabetes prevention and management. The median knowledge score increased from 60 (IQR 40–80) at pre-test to 80 (IQR 40–90) at post-test (p = 0.009). Qualitative findings revealed positive shifts in cadres’ attitudes and increased self-efficacy in communicating health information. Key themes identified included knowledge empowerment and enhanced readiness for community engagement. Follow-up observations confirmed that cadres successfully applied their new skills, such as conducting risk screenings and health education, during community Posyandu ILP sessions. A structured, participatory, and context-sensitive training program effectively enhanced the knowledge, attitudes, and practical skills of community health cadres in DM prevention. Empowering cadres through continuous mentorship and integrating such programs into local health systems offers a sustainable and scalable strategy to strengthen community resilience and advance chronic disease management. Keywords: Diabetes melitus, community health cadres, health education empowerment, non-communicable diseases primary health care. ABSTRAK Diabetes mellitus (DM) merupakan tantangan kesehatan masyarakat yang signifikan, dengan beban yang meningkat pesat di Indonesia. Kader kesehatan masyarakat (kader) memegang peran penting dalam pencegahan di tingkat masyarakat, namun banyak yang memiliki keterbatasan pengetahuan mengenai manajemen dan pencegahan DM. Program keterlibatan masyarakat ini bertujuan meningkatkan pengetahuan, sikap, dan praktik (KAP) kader kesehatan di wilayah Puskesmas Tahtul Yaman, Kota Jambi, dengan fokus pada pencegahan dan pengendalian diabetes. Program ini menggunakan pendekatan penelitian tindakan partisipatif yang melibatkan 15 kader aktif. Intervensi, yang dilaksanakan antara Agustus dan September 2025, meliputi modul pelatihan terstruktur, ceramah interaktif, Diskusi Kelompok Terfokus (FGD), simulasi berbasis keterampilan (termasuk penggunaan glukometer), serta pendistribusian paket alat edukasi. Desain pre-test/post-test digunakan untuk mengevaluasi perubahan pengetahuan, dengan analisis data menggunakan uji Wilcoxon tanda berpasangan. Data kualitatif dikumpulkan melalui sesi refleksi dan observasi lapangan satu bulan pasca-pelatihan. Peserta menunjukkan peningkatan pengetahuan yang signifikan secara statistik; skor median pengetahuan meningkat dari 60 (IQR 40–80) pada pre-test menjadi 80 (IQR 40–90) pada post-test (p = 0.009). Temuan kualitatif mengungkapkan perubahan sikap yang positif dan peningkatan efikasi diri kader dalam menyampaikan informasi kesehatan. Tema kunci yang muncul meliputi pemberdayaan pengetahuan dan kesiapan yang meningkat untuk keterlibatan masyarakat. Observasi tindak lanjut mengonfirmasi bahwa kader berhasil menerapkan keterampilan baru, seperti melakukan skrining risiko dan penyuluhan kesehatan, selama sesi Posyandu ILP di masyarakat. Program pelatihan yang terstruktur, partisipatif, dan sensitif terhadap konteks secara efektif meningkatkan pengetahuan, sikap, dan keterampilan praktis kader kesehatan masyarakat dalam pencegahan DM. Memberdayakan kader melalui pendampingan berkelanjutan dan mengintegrasikan program semacam ini ke dalam sistem kesehatan lokal menawarkan strategi yang berkelanjutan dan dapat diskalakan untuk memperkuat ketahanan komunitas dan memajukan pengelolaan penyakit kronis Kata kunci: Diabetes melitus, kader kesehatan masyarakat, pemberdayaan pendidikan kesehatan, pelayanan kesehatan primer untuk penyakit tidak menular